Luxury consumption as identity markers in Tallinn: A study of Russian and Estonian everyday identity construction through consumer citizenship. (May 2020) - Polese, Abel; Seliverstova, Oleksandra
While the importance of consumption of luxury goods as a mechanism accompanying upwards movement in a social hierarchy has been well acknowledged, attention to the role and perceptions of luxury in multicultural societies has been scarce so far. It is nonetheless intriguing that ethnic groups inhabiting the same territory, and exposed to a same culture, might develop substantially different notions of luxury, which may end up affecting the integration, or isolation, of one of the groups. Our article addresses this deficiency in the literature by exploring the case of Estonia, a multi-ethnic society where Russians make up almost one-fourth of the population. Much has been written about the integration, and lack thereof, of ethnic Russians into Estonian society. We contrast these views by looking at inter-ethnic relations in the country from a different angle and by a) looking at consumption of luxury in the country through the concept of 'conspicuous consumption'; b) endorsing Foster's concept of consumer citizenship. This allows us to shed light on an under-explored tendency and maintain here that, in a significant number of cases, ordinary citizens challenge official identity narratives by the state through counter-narratives centred around consumption of luxury at the everyday level. The identified counter-narratives end up translating into (consumer behaviour) instructions for those Russians willing to assert their Estonianness thus allowing them to seek integration into the majority group by simply consuming luxury items that they perceive as appreciated among Estonians, or associated with Estonian high status. By doing this, we make a case for expanding the parameters for academic scrutiny of social integration to include more 'banal' forms of consumer practices through which top- down narratives and macro studies may be challenged.